The Impact of the COVID-19 Pandemic and Societal Infection Control Measures on Children and Adolescents' Mental Health: A Scoping Review - Marchi, Jamile; Johansson, Nina; Sarkadi, Anna; Warner, Georgina (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic is primarily a crisis that affects people's physical health. However, it is well known from previous epidemics and pandemics that there are other indirect negative impacts on mental health, among others. The purpose of this is scoping review was to explore and summarise primary empirical research evidence on how the COVID-19 pandemic and societal infection control measures have impacted children and adolescents’ mental health. Methods: A literature search was conducted in five scientific databases: PubMed, APA PsycINFO, Web of Science, CINHAL and Social Science Premium Collection. The search string was designed using the Population (0-18 years), Exposure (COVID-19), Outcomes (mental health) framework. Mental health was defined broadly, covering mental well-being to mental disorders and psychiatric conditions. Results: Fifty-nine studies were included in the scoping review. Of these, 44 were cross-sectional and fifteen were longitudinal studies. Most studies reported negative impact of the COVID-19 pandemic on child and adolescent mental health outcomes, yet the evidence was mixed. This was also the case for studies investigating societal control measures. Strong resilience, positive emotion regulation, physical activity, parental self-efficacy, family functioning and emotional regulation, and social support were reported as protective factors. On the contrary, emotional reactivity and experiential avoidance, exposure to excessive information, COVID-19 school concerns, presence of COVID-19 cases in the community, parental mental health problems, and high internet, social media and video game use were all identified as potentially harmful factors. Conclusions: Due to the methodological heterogeneity of the studies, it is challenging to draw definitive conclusions about the real impact of the COVID-19 pandemic on the mental health of children and adolescents. However, the existing body of research gives some insight to how parents, clinicians and policy makers can take action to mitigate the effects of COVID-19 and control measures.